1997
DOI: 10.1016/s0896-6273(00)80391-8
|View full text |Cite
|
Sign up to set email alerts
|

Xath5 Participates in a Network of bHLH Genes in the Developing Xenopus Retina

Abstract: We examined the function of basic-helix-loop-helix (bHLH) transcription factors during retinal neurogenesis. We identified Xath5, a Xenopus bHLH gene related to Drosophila atonal, which is expressed in the developing Xenopus retina. Targeted expression of Xath5 in retinal progenitor cells biased the differentiation of these cells toward a ganglion cell fate, suggesting that Xath5 can regulate the differentiation of retinal neurons. We examined the relationship between the three bHLH genes Xash3, NeuroD, and Xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
207
2
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(227 citation statements)
references
References 56 publications
17
207
2
1
Order By: Relevance
“…Xath5 misexpressing embryos had ectopic N-tubulin staining throughout the injected side (100%, n ϭ 27, Fig. 2G), indicating that Xath5 can promote neurogenesis, as previously described (Kanekar et al, 1997). N-tubulin staining was largely restricted to the developing nervous system on the uninjected side (Fig.…”
Section: Overexpression Of Xath5 Expands the Region Of Xenopus Olfactsupporting
confidence: 77%
See 3 more Smart Citations
“…Xath5 misexpressing embryos had ectopic N-tubulin staining throughout the injected side (100%, n ϭ 27, Fig. 2G), indicating that Xath5 can promote neurogenesis, as previously described (Kanekar et al, 1997). N-tubulin staining was largely restricted to the developing nervous system on the uninjected side (Fig.…”
Section: Overexpression Of Xath5 Expands the Region Of Xenopus Olfactsupporting
confidence: 77%
“…Paradoxically, we have previously shown that overexpression of XNeuroD causes an expansion of Xath5 expression in anterior of the embryo (Kanekar et al, 1997), raising the question of why Xath5 promotes expanded Xomp2 expression when overexpressed by RNA injection, but not when its expression is activated after XNeuroD overexpression. XNeuroD may be activating the expression of additional genes that may interfere with ORN differentiation, such as negative regulatory factors.…”
Section: Xath5 Can Regulate Olfactory Neurogenesismentioning
confidence: 98%
See 2 more Smart Citations
“…(Carl, et al, 2002, Mathers and Jamrich, 2000, Porter, et al, 1997 The bHLH (basic Helix Loop Helix) gene family of transcription factors also has pivotal roles in the unique patterning of transcription factors that guide retinal development (Mash1, Math3, Ngn2). (Akagi, et al, 2004, Brown, et al, 1998, Brown, et al, 2001, Hojo, et al, 2000, Kanekar, et al, 1997, Marquardt and Gruss, 2002, Moore, et al, 2002, Morrow, et al, 1999, Yan and Wang, 1998 Several transcription factors are clearly essential for photoreceptor development, and their mutations cause retinal degenerations: NRL, CRX, Otx2, Trβ2 (thyroid hormone receptor β2), and NR2E3. (Bessant, et al, 1999, DeAngelis, et al, 2002, Freund, et al, 1997, Haider, et al, 2000, Haider, et al, 2001, Martinez-Gimeno, et al, 2001, Ng, et al, 2001, Nishida, et al, 2003, Swain, et al, 1997 However, our knowledge of the interactions of these cell-specific proteins with each other and upstream signal transduction proteins remains sparse.…”
Section: Introductionmentioning
confidence: 99%